Doves, Diplomats, and Diabetes : a Darwinian interpretation of type 2 diabetes and related disorders - Watve, Milind (Springer, 2013)
Although the thought that the origins of obesity and type 2 diabetes might lie in our hunter gatherer adaptations is not new, research over the last decade makes us rethink many of the classical concepts. Brain and behavior is increasingly being recognized as central to all the endocrine, metabolic and immunological changes that earmark type 2 diabetes and other metabolic syndrome disorders. A major change in paradigm appears to be on the horizon and this book intends to speed up the paradigm shift by raising important questions, pointing out flaws and inadequacies in the prevalent paradigm and stimulating radical rethinking which would redirect and refine the line of research as well as bring some fundamental changes in drug discovery and clinical practice--